Comparison of survival outcomes between squamous cell carcinoma and adenocarcinoma/adenosquamous carcinoma of the cervix after radical radiotherapy and chemotherapy - Ping Liu; Mei Ji; Yanxiang Kong; Zhifeng Huo; Qiubo Lv; Qinghuang Xie; Danbo Wang; Biliang Chen; Hailin Wang; Zhumei Cui; Qianqing Wang; Xiaonong Bin; et al. (BMC Cancer, 2022)
Abstract Background This study aimed to compare the survival outcomes between squamous cell carcinoma (SCC) and adenocarcinoma/adenosquamous carcinoma (AC/ASC) of the cervix after radical radiotherapy and chemotherapy. Methods Propensity score matching (1:4) was used to compare overall survival (OS) and disease-free survival (DFS) in cervical cancer patients with SCC and AC/ASC in China. Results Five thousand four hundred sixty-six patients were enrolled according to the criteria. The 5-year OS and DFS in the SCC group (n = 5251) were higher than those in the AC/ASC group (n = 215). After PSM (1:4), the 5-year OS and DFS in the SCC group were higher than those in the AC/ASC group (72.2% vs 56.9%, p < 0.001, HR = 1.895; 67.6% vs 47.8%, p < 0.001, HR = 2.056). In stage I-IIA2 patients, after PSM (1:4), there was no significant difference in 5-year OS between the SCC group (n = 143) and the AC/ASC group (n = 34) (68.5% vs 67.8%, P = 0.175). However, the 5-year DFS in the SCC group was higher than that in the AC/ASC group (71.0% vs 55.7%, P = 0.045; HR = 2.037, P = 0.033). In stage IIB-IV patients, after PSM (1:4), the 5-year OS and DFS in the SCC group (n = 690) were higher than those in the AC/ASC group (n = 173) (70.7% vs 54.3% P < 0.001 vs 1.940%, P < 0.001 vs 45.8%, p < 0.001). Conclusions For stage I-IIA2, there was no significant difference in 5-year survival time, but patients with AC/ASC were more likely to relapse. In the more advanced IIB-IV stage, the oncological outcome of radical radiotherapy and chemotherapy of cervical AC/ASC was worse than that of SCC.